2012
DOI: 10.4236/epe.2012.44039
|View full text |Cite
|
Sign up to set email alerts
|

Global Impact of Gas Flaring

Abstract: This work deals with the multi-faceted impact of gas flaring on a global scale and the different approach employed by researchers to measure gas flared and its resulting emissions. It gives an overview of methods employed by these researchers in the oil and gas industry, academia and governments in attempt to determine ways of measuring and reducing gas flaring and its emission drastically. This approach so far includes analytical studies, numerical studies, modeling, computer simulations, etc. the goal behind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
95
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(96 citation statements)
references
References 21 publications
0
95
0
1
Order By: Relevance
“…Amann et al demonstrated that controlling emission during oil and gas production would substantially reduce premature deaths caused by air pollution (Amann et al, 2017). Evidence in many literature on the impact of gas flares such as Ismail and Umukoro (2012), Roland (2010) and Gobo et al (2009) show consistency that gas flare has a severe effect on human health.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Amann et al demonstrated that controlling emission during oil and gas production would substantially reduce premature deaths caused by air pollution (Amann et al, 2017). Evidence in many literature on the impact of gas flares such as Ismail and Umukoro (2012), Roland (2010) and Gobo et al (2009) show consistency that gas flare has a severe effect on human health.…”
Section: Literature Reviewmentioning
confidence: 99%
“…So, for every thousand cubic feet of gas burned, some dollars or work hours are wasted. Ismail and Umukoro (2012) argued that the economic cost of gas flaring is staggering hence a gas intensive modes of production holds greater opportunities for private sector investment (pp. 293).…”
Section: Economic Environmental and Public Health Impact Of Gas Flaringmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of the foregoing, there exists a growing body of work on liabilities such as gas flaring in the study area and these include Raimi [11] Ismail [12], Oseji [13], Ubani [14] and others. From these studies, [12] saw gas flaring as a local and global concern and one of the most challenging energy and environmental problems.…”
Section: Introductionmentioning
confidence: 99%
“…Fuel gas is often composed of hydrocarbons (methane, ethane, propane and butane), hydrogen, and carbon monoxide, which have large heating values [10]. In most cases, these fuels are flared to the atmosphere, leading to detrimental effects on the environment and loss of heating values [11,12].…”
Section: Introductionmentioning
confidence: 99%